Relevance of Eutagolics in the Development of Professional and Pedagogical Competencies - Karimova Nozima Nurmuhamadovna (Researchparks Publishing, 2022)
The article deals with the dynamics of change in the trajectory of education in the XX and XXI centuries (pedagogy - androgogy - eutogogy). It also substantiates the importance of eutagogy in the continuous training of teachers and the organization of need-based education, the importance of eutagogy in the development of continuous professional skills of teachers.